(untitled) (Asian Journal of Pharmaceutics (AJP), 2026)
Introduction: Generalized anxiety disorder (GAD) is a psychological illness associated with uncontrollable worry about everything. They have symptoms such as restlessness, worry, difficulty concentrating, insomnia, lightheadedness, and an elevated heart rate. Globally, primary healthcare expects the prevalence to range from 2.4% to 31.2%. Females are more likely to be affected by GAD than males. Objectives: The main objective of this study is to determine the prevalence of GAD among the general population in Saudi Arabia. In addition, we identify the related risk factors to GAD. Methodology: This is a cross-sectional observational study regarding the prevalence of associated risk factors among the general population. In Saudi Arabia During the period ranging from 2024 Aug to 2025 February. We included male and female citizens of Saudi Arabia living in Saudi Arabia. With the exclusion of the residents of Saudi Arabia and citizens who don’t reside in Saudi Arabia. Two parts of a computerized self-administered questionnaire were used to evaluate participants for GAD. The sample size that was determined was 385, with an indicator percentage of 0.50, a margin of error of 5%, and a confidence interval of 95%.